Investigation of Efficient Pullulan Synthesis Utilizing Huangjiu Lees as a Substrate - Peiqi Lu; Tiantian Liu; Jingqiu Ma; Tao Kan; Xiao Han; Zhongwei Ji; Jian Mao (Foods)
Pullulan is a high-value biopolymer synthesized by Aureobasidium pullulans through the fermentation of starch and sugars. It finds extensive applications in food, packaging, biomedicine, and other sectors. However, the high production costs significantly limit the development and application of pullulan. Consequently, there is an urgent need to identify high-quality fermentation substrates. In recent years, the rapid growth of Huangjiu industry has led to the generation of waste Huangjiu lees, which not only contribute to environmental pollution but also represent a significant waste of resources. As a result, the resource utilization of Huangjiu lees has garnered considerable attention. In this study, Huangjiu lees were employed as raw materials for fermentation to produce pullulan. Following fermentation of Huangjiu lees powder with the primary strain Aureobasidium pullulans LL1, the yield of pullulan was notably reduced. Through adaptive evolution, an evolved strain, Aureobasidium pullulans AP9, was isolated, demonstrating enhanced efficiency in producing pullulan from Huangjiu lees. The impact of Huangjiu lees on pullulan biosynthesis was elucidated via transcriptome analysis. Fermentation conditions were optimized using a single-factor approach, and a multi-strain staged fermentation strategy involving Aspergillus niger and Aureobasidium pullulans was employed to further enhance pullulan yield. Under optimal conditions, the pullulan yield reached 22.06 g/L, with a molecular weight of 1.04 × 106 Da. This study underscores the significant potential of utilizing Huangjiu lees for pullulan production and offers valuable insights for the resource utilization of this byproduct.